A review of elastocaloric cooling: Materials, cycles and system integrations. (April 2016) - Qian, Suxin; Geng, Yunlong; Wang, Yi; Ling, Jiazhen; Hwang, Yunho; Radermacher, Reinhard; Takeuchi, Ichiro; Cui, Jun
Highlights: Reviewed elastocaloric cooling materials and quantitatively assessed half of them. Discussed thermodynamic cycle options for elastocaloric cooling. Reviewed four key aspects of developing a successful elastocaloric cooling system. Summarized the up-to-date development status of elastocaloric cooling prototypes. Abstract: Elastocaloric cooling is a new alternative solid-state cooling technology undergoing early stage research and development. This study presents a comprehensive review of key issues related to achieving a successful elastocaloric cooling system. Fundamentals in elastocaloric materials are reviewed. The basic and advanced thermodynamic cycles are presented based on analogy from other solid-state cooling technologies. System integration issues are discussed to characterize the next generation elastocaloric cooling prototype. Knowledge acquired from the elastocaloric heat engines is provided as the basis for the design of cooling system configuration. Commercially available drivers enabling proper compression and tension are also presented. A few performance assessment indices are proposed and discussed as guidelines for design and evaluation of future elastocaloric cooling system. A brief summary of the up-to-date elastocaloric cooling prototypes is presented as well.